FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA KARYAWAN DI PROYEK PLTGU MUARA TAWAR PT HUTAMA KARYA KABUPATEN BEKASI TAHUN 2020 - Annisa Tria Widiaty (2021)
Workplace is one of those places where stressors can develop. Occupational stress is a common thing that can be experienced by the employees. Occupatinal stress can be caused due to the inability of the employees to meet demands to complete their work or the feeling of discomfort and dissatisfaction at work. Lots of workloads, short period of time, poor communication between employees, and other factors can be the source of occupational stress. The purpose of this study was to determine the factors associated with occupational stress among employees at PLTGU Muara Tawar Project PT Hutama Karya. This was a quantitative analytic research with cross-sectional design. The sample of this research was 118 employees at PLTGU Muara Tawar Project PT Hutama Karya. The results showed that 89 employees experienced mild stress. The results of this study showed that the length of employment (p-value = 0.049), and work relationships (p-value = 0.005) were associated with occupational stress. Therefore, employees are recommended to apply stress management in order to prevent stress as early as possible, make the best of their worktime, and do social interactions between employees to create a good work relationships.